7. Productivity And Chemical Composition Of Several Mulberry Species (Morus spp) Agains Spacing Plant, and Cutting Age - Rijanto Hutasoit; Simon Ginting; Juniar Sirait; Andi Tarigan (The Faculty of Veterinary Medicine of Syiah Kuala University, 2016)
The cultivation of mulberry as forages is scarce in Indonesian feeding system for ruminant production, although many studies have indicated its nutritional potential as animal feed especially ruminants. This study was aimed to investigate the effects spacing of plant and cutting age on productivity and chemical composition of some species mulberry plants. The experiment was conducted in a randomized block design with factorial treatments. The factors species were (M. indica cv kanva, M. nigra, M. cathyana, and M. Multicaulis), the spacing of plants (1 x 0.5 m, 1 x 1 m and 1 x 1.5 m) and cutting ages (210, 240, and 270 days after planting). The results showed that species, M. multicaulis and M. cathyana are the highest growth, using a spacing of 1 x 0.5 m with cutting age 270 days after planting. Dry matter production highest (P 0,05) in M. Cathyana at spacing of 1 x 0.5 with cutting age 270 days after planting. The ratio of leaves and stems of plants are affected by age, the highest proportions of leaf is obtained at the cutting age of 210 days. Chemical composition were highest in M.multicaulis at the age of 270 days. The highest content of organic matter (OM) were found in M.Kanva and not different with M. Nigra at the age of 270 day after planting. In treatment of cutting ages have no effect (P 0.05) on the Crude protein (CP), ADF, NDF, lignin and tannin content. The average content of CP obtained gained 20.69%, 32.38% ADF, NDF 33.99%, 12.45% lignin and tannin 0.3%. Concluded that mulberry plants with a plant spacing of plant 1 x 0.5 and 270 days after plant have more advantages for use as animal feed.